Tests of the overreaction hypothesis and the timing of mean reversals on the JSE Securities Exchange (JSE): The case of South Africa - Heng-hsing Hsieh; Kathleen Hodnett (Journal of Applied Finance & Banking, 2011)
This paper examines the overreaction hypothesis on the JSE Securities Exchange (JSE) documented by Page and Way [5] and Muller [4] over a longer and more recent period from 01 January 1993 to 31 March 2009. The mean reversals due to investor overreaction are found to be stronger for the past winner and loser portfolios with longer formation periods. Similar to the results of De Bondt and Thaler [1] and Page and Way [5], the loser portfolios exhibit stronger mean reversals than their winner counterparts over the examination period. The delayed mean reversals for the winner portfolios might be attributable to behavioral biases such as fear of regret or being reference dependent, which cause investors to hold on too long to the past winners. The strength of mean reversals is found to be cyclical and fluctuates around the South African business cycle. Study results also suggest that contrarian investing could be a safe haven during the financial market turmoil due to their low correlations with the market during the economic downturn.
Keywords: G11; 330; overreaction; mean reversal; market timing; contrarian; momentum